2017
DOI: 10.1016/j.ijantimicag.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Confirming model-predicted pharmacokinetic interactions between bedaquiline and lopinavir/ritonavir or nevirapine in patients with HIV and drug-resistant tuberculosis

Abstract: Bedaquiline and its metabolite M2 are metabolised by CYP3A4. The antiretrovirals ritonavir-boosted lopinavir (LPV/r) and nevirapine inhibit and induce CYP3A4, respectively. Here we aimed to quantify nevirapine and LPV/r drug-drug interaction effects on bedaquiline and M2 in patients co-infected with HIV and multidrug-resistant tuberculosis (MDR-TB) using population pharmacokinetic (PK) analysis and compare these with model-based predictions from single-dose studies in subjects without TB. An observational PK s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 18 publications
0
49
2
3
Order By: Relevance
“…This CYP P450-mediated metabolism opens the issue of DDIs with ARVs [39]. BRILL et al [39] observed that bedaquiline clearance was reduced by NVP to 82% and M2 clearance increased to 119% of their original values, underpinning no clinically significant interactions. Conversely, LPV/r significantly reduced both bedaquiline and M2 clearance, increasing their concentrations.…”
Section: Bedaquilinementioning
confidence: 99%
See 2 more Smart Citations
“…This CYP P450-mediated metabolism opens the issue of DDIs with ARVs [39]. BRILL et al [39] observed that bedaquiline clearance was reduced by NVP to 82% and M2 clearance increased to 119% of their original values, underpinning no clinically significant interactions. Conversely, LPV/r significantly reduced both bedaquiline and M2 clearance, increasing their concentrations.…”
Section: Bedaquilinementioning
confidence: 99%
“…Information about cardiac safety of bedaquiline in association with clofazimine or fluoroquinolones is still scanty [37]. The GUGLIELMETTI et al [35] study suggests that co-administration of clofazimine is not associated with QTc prolongation, while the administration of both high-dose moxifloxacin and methadone was associated with QTcF values >500 ms. New information on drug-drug interactions (DDIs) with antiretrovirals (ARVs) like lopinavir/ritonavir (LPV/r) and nevirapine (NVP) can be retrieved from pharmacokinetic (PK) studies [38,39]. The PK profile of bedaquiline is characterised by extensive tissue distribution and an extremely long terminal half-life, exceeding 5 months [40].…”
Section: Bedaquilinementioning
confidence: 99%
See 1 more Smart Citation
“…Bedaquiline, which is metabolized by CYP 3A4, can be used with nevirapine (and presumably with raltegravir or dolutegravir). Efavirenz reduces and ritonavir‐boosted lopinavir increases bedaquiline concentrations, yet the clinical relevance of these interactions and the effectiveness of potential dose modifications in mitigating the DDIs has not been explored in patients . Dosing for bedaquiline in children is still being established; the magnitude of DDIs with this drug and efavirenz or ritonavir‐boosted lopinavir for children cannot be extrapolated directly from adult studies, particularly for children aged <5 years, in whom expression of CYP3A isoforms is different from adults and varies by age.…”
Section: Childhoodmentioning
confidence: 99%
“…Efavirenz reduces and ritonavir-boosted lopinavir increases bedaquiline concentrations, yet the clinical relevance of these interactions and the effectiveness of potential dose modifications in mitigating the DDIs has not been explored in patients. [59][60][61] Dosing for bedaquiline in children is still being established; the magnitude of DDIs with this drug and efavirenz or ritonavir-boosted lopinavir for children cannot be extrapolated directly from adult studies, particularly for children aged <5 years, in whom expression of CYP3A isoforms is different from adults and varies by age. Mechanistic models or models that consider CYP3A maturation function are available to predict drug PKs in children but not to predict the effects of inducers or inhibitors of CYP3A on substrates of that enzyme.…”
Section: New Drugsmentioning
confidence: 99%